GROWTH PATTERN OF FRESHWATER PRAWN (ATYA GABONENSIS GIEBEL, 1875 (CRUSTACEA: ATYIDAE) IN THE LOWER RIVER BENUE, MAKURDI, NIGERIA - OBETTA, C.; CHEIKYULA, J.O.; YUSUF, A.; AKISANI, C. A.; MBATA, U. F. (Nigerian Journal of Fisheries, 2022)
The growth pattern of freshwater prawn (Atya gabonensis) in the lower river Benue, Makurdi, Nigeria was carried out. A total of 1,030 Specimens of Atya gabonensis were collected with the aid of fishermen from January to August 2015. These were transported in an ice box to the laboratory for further studies. The length-weight relationship was calculated as described by Bagenal. The condition factor was calculated using an equation by Ricker. The allometric coefficient ‘b’ was highest in August (3.114)and lowest in February(1.119). The mean condition factor (K) was highest in May (2.99 ± 0.08)and lowest in March (2.25 ± 0.05).Carapace length ranged from 0.90cm in February to 6.20cm in June(mean =2.31±0.04cm).Total length ranged from 3.0cm in February to 14.4 cm in January (mean=8.55±0.06cm) and body weight ranged from 1.50g in March to 73.0g in January with a mean value of 18.03±0.38g. Correlation ranged from 0.8025 in June to 0.9550 in January. It was concluded that A. gabonensis is well adapted to the freshwater body of River Benue and it is suspected to make a good candidate for prawn culture in the freshwater system in Nigeria.